Development and investigation of dual potent anticancer drug-loaded nanoparticles for the treatment of lung cancer therapy. (July 2021) - Zhou, Ning; Wang, Weihua; Li, Hanyue; Jiang, Daowen; Zhong, Xiao
Graphical abstract: Highlights: Fabrication of Gemcitabine and 5-Fluorouracil drugs encapsulated with polymeric nanoparticles. The in vitro antiproliferative activity shows GEM-5FU NPs induced apoptosis in human lung cancer cells. The morphological observations of GEM-5FU NPs have examined biochemical staining techniques. The cell death of GEM-5FU NPs was confirmed by flow cytometry analysis. Abstract: Combinations of two potent chemotherapeutic drugs are often used to treat early stage lung cancer. To enhance the efficiency of the treatment, a combinational co-drug delivery system of gemcitabine (GEM) and 5-fluorouracil (5FU) is used owing to its great antitumor ability, as GEM and 5FU improve the anticancer ability of lung cells by stabilizing the tumor microenvironment. Nevertheless, encapsulation of GEM and 5FU potential anticancer drugs by co-loaded poly(lactic-co-glycolic acid) (PLGA)- Polyethylene glycol (PEG) nanoparticles (NPs) is not effective because of the incompatibility of the dual drug GEM and 5FU polymeric biodegradable system. Transmission electron microscopy was used to examine the morphology of GEM NPs, 5FU NPs, and GEM-5FU NPs, along with their nanoparticle morphology and size. GEM-5FU NPs also induced apoptosis in vitro in human lung cells such as A549 and HEL-299. Morphological changes and cell deaths were the result of different biochemical staining techniques such as acridine orange-ethidium bromide (AO-EB) and Hoechst staining. In addition, the mechanistic investigation of cell death was confirmed by Annexin V-Fluorescein isothiocyanate (FITC) using flow cytometry. Taken together, this dual co-drug delivery method revealed that GEM-5FU NPs might have a remarkable potential to enhance the efficacy of lung cancer therapy.